Analyzing the use of iMocha Assessment Platform for hiring and evaluation at IDLC Finance Limited: a comparative study - Chowdhury, Mustaquim Rahman (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.